Pengembangan Alat Bantu Pemasang Dan Pelepas Penambat E-Clip Berbasis Dongkrak Elektrik - Dadang Sanjaya Atmaja; Henry Widya Prasetya; Yusuf Adhisuryo (Virtual of Mechanical Engineering Article, 2022)
Abstract The fastener is one of the most important components in the railway infrastructure that must be inspected and maintained. Installing and removing fasteners nowadays is still using manual tools like hammers and panpullers which take a long time of 12 seconds and can damage the bearings due to the rebound of the tool. And the current tool is a hydraulic pump-based e-clip fastener installation and removal tool that takes 22 seconds to remove the fastener. Therefore, a device is needed to minimize the damage on the bearing so that its use is more effective and its utility is easy because it uses a control switch that is connected to the battery and then connected to an electric jack. This tool is targeted to be able to release the fastening in a period of under 10 seconds.The process of making an electric jack-based e-clip fastener assisting tool can be carried out in several stages, each of which is the design process, the upper frame manufacturing process, the lower frame manufacturing process, the tool pusher frame manufacturing process, the tool balancer frame manufacturing process, and the completion process. The finishing process of the tool manufacturing.The function testing of the electric jack-based e-clip fastener installation and removal assisting tool at Indonesian Railways Company, Rail road unit, Madiun for road and bridge maintenance. Function testing is done twice with two different operators. The results of the tool function test, the tool can perform the process of releasing one fastener for 5 seconds and can speed up the fastening maintenance process at Indonesian Railways Company, Rail road unit, Madiun. Keyword: E-clip Mounting, Rail Maintenance, Electric.